Mesenteric Artery Insufficiency - Coles, John C. (1963)
The syndromes of superior mesenteric artery insufficiency are briefly reviewed. Three cases associated with infarction of bowel which were treated with restoration of arterial flow and resection of residual irretrievable bowel are reported. In two patients an embolectomy and in one patient a bypass graft were used to restore arterial continuity. The importance of the recognition and removal of irretrievable bowel at the time of vascular reconstruction is emphasized. Success is not necessarily predicated by the time factor alone, although the importance of early diagnosis and surgical intervention cannot be denied.